The Change of the Supervision of the Activities of Economic Operators - Šilvaitė, Eimantė (Teisė, 2021)
The present article analyses the essence and purpose of the supervision of the activities of economic operators as a field of public administration, as well as its expression and evaluation in national administrative law. It raises the question of whether there has been a paradigmatic shift in the supervision of the activities of economic operators and in what ways it is being expressed.